Articulating Our Very Unfreedom: The Impossibility of Refusal in the Contemporary Academy - Zvyagintseva, Lydia (Canadian Journal of Academic Librarianship / Revue canadienne de bibliothéconomie universitaire)

(untitled) (Canadian Association of Professional Academic Librarians / Association Canadienne des Bibliothécaires en Enseignement Supérieur, 2021)
This paper begins and ends with a provocation: I argue that refusal in librarianship is both impossible and necessary. Reviewing examples of crisis narratives which permeate both American and Canadian universities, I take a materialist perspective on the idea of refusal within academic librarianship. To do so, I draw on the work of Audra Simpson, Kyle Whyte, Eve Tuck, Mario Tronti, and Rinaldo Walcott to examine the sites of impossibility of refusal in the practice of academic librarianship within contemporary neoliberal education institutions. Then, I analyze the totality of capitalism in setting the limit for the practice of refusal through case studies of direct action, including the Icelandic Women’s Strike of 1975 and the 2020 Scholar Strike Canada. Finally, I identify private property and history as key frames for understanding the contradiction at the heart of refusal of crisis. As such, any refusal that does not address the centrality of labour and private property relations can thus be understood as harm reduction rather than emancipation. Ultimately, I argue that for librarians to refuse would require an abandonment of liberalism as librarianship’s guiding philosophy, and a redefinition of librarianship as such.